THEORETICAL ASPECTS OF INFLATION TARGETING - Obradović, Jelena; Dinić, Vladimir; Pivašević, Jelena (International Journal of Economic Practice and Policy, 2014)
Inflation targeting is one of the possible strategies used by central banks during conducting monetary policy. The basic characteristics, advantages and disadvantages of inflation targeting will be presented in this paper. The focus is on the the presentation and interpretation of the understanding of this strategy from the perspective of monetarist and Keynesian theory, the theory of rational expectations, and methodological analysis of the strategy in light of the game theory using payoff matrix.